IMPROVEMENT OF EDIBLE BIOPOLYMER FILM PRODUCTION TECHNOLOGY AND INVESTIGATION OF ITS BIODEGRADATION PROCESS - S.N.Obloberdiyev,; G.Sh.Korabekova,; F.Sh.G‘ulomova,; M.J.Bekmurodova,; Sh.E.Ulashova,; Z.A.Madusmonova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This study focuses on improving the production technology of edible biopolymer films and investigating their biodegradation process. The research evaluates the formation of a thin, flexible and environmentally safe film suitable for food packaging applications. Special attention is given to technological parameters, film-forming properties, physical appearance, usability, and natural degradation under environmental conditions. The obtained results may contribute to the development of eco-friendly, biodegradable and safe packaging materials as an alternative to synthetic plastic films.